Lending Growth As A Fiqh Implication Toward Product Development Of Islamic Bank In Indonesia - ., Indupurnahayu; Prasetyowati, Riris Aishah (Archives of Business Research, 2018)
This study aim to examine the financing growth of Islamic bank in Indonesia with the provisions system and proof that there is a counterclicality and capital smoothing behavior of bank manager, these findings contrast with the results of previous studies on procyclical behavior in loan loss provisions. The objects of this study are Islamic Banks and Islamic Business Unit in Indonesia period of 2000 – 2016. This study specifically estimates a different calculation in every component of discretionary and non-discretionary in Islamic bank financing with the variable control such as, non performance loan/financing, total loan, deposit growth, equity ratio, and total asset. The equation will be tested by using the regression system estimation and the validity tested by Kolmogorov-Smirnov test and Durbin Watson. The result of this study quantitatively proved that there is a pattern of countercyclicality behavior in Islamic bank consistent with compliant Syariah and significantly has positive correlation described by the relation of loan loss provision with the coefficient of GDP growth rate. From this result in accordance with the fiqh platform, for all forms of muamalah is “al ashlu fil mu’amalah illa al-ibahah yadullu daliil ‘alaa tahriimiha” (the origin of everything is allowed unless there is proof that forbid it), which means that by using the theory of fiqh rules the product development of Islamic bank can be done and expanded. The evidence for financing growth is that Islamic bank financing does not depend on the amount of deposit rates, and the coefficient of deposit and financing growth is insignificant and excluded, while the growth of financing and bank capital, GDP, and NPL have a negative and significant correlation. The coefficient of total assets and the growth of financing has a positive and significant correlation that means that Islamic bank managers to be income smoothing behavior.